(untitled) (Communications in Computational Chemistry, 2025)
Gout is a common chronic disease caused by the deposition of monosodium urate crystals. Previous studies confirmed the anti-gout effects of sunflower receptacles. For example, eupatoriochromene may be one of the most important compounds for reducing uric acid and relieving gout, which can be extracted from the essential oil of sunflower receptacles (EOSR). However, the other active components in EOSR and their anti-gout molecular mechanisms remain unclear. In this work, we employed widespread methods such as network pharmacology, machine learning algorithm, molecular docking, and molecular dynamics simulation, to investigate the anti-gout molecular mechanisms of the EOSR components. The protein-protein interaction (PPI) network confirmed that the components of EOSR exert anti-gout effects mainly by targeting inflammatory targets. GO and KEGG enrichment analyses revealed that the components of EOSR play roles in several important biological pathways, potentially providing anti-gout effects through various mechanisms. Additionally, since the target URAT1 plays a critical role in the treatment of gout, we investigated the interactions between two components of EOSR, Linoleic acid (La) and Kauren-19-oic acid (Koa), and target URAT1 using machine learning algorithm, molecular docking and molecular dynamics simulation. It confirmed that La and Koa can stably bind to URAT1 and shift its conformation to the Inward-facing state. Similar to the positive control Benzbromarone (Ben), both La and Koa induce secondary structural changes in URAT1, with Koa sharing key residues with Ben. This research further indicates the molecular mechanisms of EOSR in treating gout and expands the range of therapeutic agents for it.